Current clinical practice: differential management of uveal melanoma in the era of molecular tumor analyses - Aaberg Jr TM (Dove Medical Press, 2014)
Thomas M Aaberg Jr,1 Robert W Cook,2 Kristen Oelschlager,2 Derek Maetzold,2 P Kumar Rao,3 John O Mason III41Michigan State University Medical School and Retina Specialists of Michigan, Grand Rapids, MI, 2Castle Biosciences, Friendswood, TX, 3Washington University School of Medicine in St Louis, St Louis, MO, 4Retina Consultants of Alabama and University of Alabama Birmingham, Birmingham, AL, USA Objective: Assess current clinical practices for uveal melanoma (UM) and the impact of molecular prognostic testing on treatment decisions.Design: Cross-sectional survey and sequential medical records review.Participants: Ophthalmologists who treat UM.Methods: (A) Medical records review of all Medicare beneficiaries tested by UM gene expression profile in 2012, conducted under an institutional review board-approved protocol. (B) 109 ophthalmologists specializing in the treatment of UM were invited to participate in 24-question survey in 2012; 72 were invited to participate in a 23-question survey in 2014.Main outcome measures: Responses analyzed by descriptive statistics, frequency analyses (percentages, Tukey, histograms), and Fisher’s exact test. Descriptive presentation of essay answers.Results: The review of Medicare medical records included 191 evaluable patients, 88 (46%) with documented medical treatment actions or institutional policies related to surveillance plans. Of these 88, all gene expression profiling (GEP) Class 1 UM patients were treated with low-intensity surveillance. All GEP Class 2 UM patients were treated with high-intensity surveillance (P<0.0001 versus Class 1). There were 36 (19%) with information concerning referrals after initial diagnosis. Of these 36, all 23 Class 2 patients were referred to medical oncology; however, none of the 13 Class 1 patients were referred (P<0.0001 versus Class 1). Only Class 2 patients were recommended for adjunctive treatment regimens. 2012 survey: 50 respondents with an annual median of 35 new UM patients. The majority of respondents (82%) performed molecular analysis of UM tumors after fine needle biopsy (FNAB); median: 15 FNAB per year; 2014 survey: 35 respondents with an annual median of 30 new UM patients. The majority offered molecular analyses of UM tumor samples to most patients. Patients with low metastatic risk (disomy 3 or GEP Class 1) were generally assigned to less frequent (every 6 or 12 months) and less intensive clinical visits. Patients with high metastatic risk (monosomy 3 or GEP Class 2) were assigned to more frequent surveillance with hepatic imaging and liver function testing every 3–6 months. High-risk patients were considered more suitable for adjuvant treatment protocols.Conclusion: The majority of ophthalmologists treating UM have adopted molecular diagnostic tests for the purpose of designing risk-appropriate treatment strategies.Keywords: uveal melanoma, gene expression profiling (GEP), medicare, molecular diagnostic test